"We Are All Distance Learners Now": How Distance Learning Informed a Library Team's Response to the Covid-19 Pandemic. Issue 2 (3rd April 2021) - Wheeler, Alex; Kyprianou-Chavda, Voula
Abstract: This article explores the response of the Science and Engineering Library team at Manchester Metropolitan University to the Covid-19 pandemic. It examines how the team's experience supporting distance-learning programmes acted as both a dress rehearsal and a road map for Library provision during the pandemic. In particular, the changing role of staff members whilst operating in the Covid-19 setting is carefully reflected upon. The article is structured into three sections, discussing support for distance-learning programmes, distance learning and Covid-19, and the changes Covid-19 prompted within the team's operation.